Dampak Gadget pada Perubahan Sosial dan Perilaku Manusia Modern - Nurfausia Wahyuningsih; Dimas Mulyadin; Nur Riswandy Marsuki (Universitas 45 Surabaya, 2024)
Technological developments in the 21st century that are very prominent are communication and information technology. This research uses qualitative research methods with a library study approach. Literature study is all efforts made by researchers to collect information that is relevant to the topic or problem that will be or is being researched. Gadgets are communication tools that are used to make things easier in everyday life, but there are several benefits and disadvantages caused by the gadget itself depending on the use of the gadget. The ultimate goal of applying qualitative research methods is to describe or explain a phenomenon in depth and systematically which is done by collecting data in depth. The research results show that technology provides many conveniences, as well as new ways of carrying out human activities. The use of technology in life has various impacts, the positive being a decrease in concentration when studying. The hope of this article is to provide in-depth insight to parents and educators about how technological advances affect life.